Pharmacokinetic interaction between etravirine or darunavir/ritonavir and artemether/lumefantrine in healthy volunteers: a two‐panel, two‐way, two‐period, randomized trial. Issue 7 (26th February 2013) - Kakuda, TN; DeMasi, R; van, Y; Mohammed, P
<x xml:space="preserve">Abstract</x> Objectives Etravirine is a substrate and inducer of cytochrome P450 (CYP) 3A and a substrate and inhibitor of CYP2C9 and CYPC2C19. Darunavir/ritonavir is a substrate and inhibitor of CYP3A. Artemether and lumefantrine are primarily metabolized by CYP3A; artemether is also metabolized to a lesser extent by CYP2B6, CYP2C9 and CYP2C19. Artemether has an active metabolite, dihydroartemisinin. The objective was to investigate pharmacokinetic interactions between darunavir/ritonavir or etravirine and arthemether/lumefrantrine. Methods This single‐centre, randomized, two‐way, two‐period cross‐over study included 33 healthy volunteers. In panel 1, 17 healthy volunteers received two treatments (A and B) in random order, with a washout period of 4 weeks between treatments: treatment A: artemether/lumefantrine 80/480 mg alone, in a 3‐day course; treatment B: etravirine 200 mg twice a day (bid) for 21 days with artemether/lumefantrine 80/480 mg from day 8 (a 3‐day treatment course). In panel 2, another 16 healthy volunteers received two treatments, similar to those in panel 1 but instead of etravirine, darunavir/ritonavir 600/100 mg bid was given. Results Overall, 28 of the 33 volunteers completed the study. Co‐administration of etravirine reduced the area under the plasma concentration–time curve (AUC) of artemether [by 38%; 90% confidence interval (CI) 0.48–0.80], dihydroartemisinin (by 15%; 90% CI 0.75–0.97) and lumefantrine (by 13%; 90% CI 0.77–0.98) at steady state. Co‐administration of darunavir/ritonavir reduced the AUC of artemether (by 16%; 90% CI 0.69–1.02) and dihydroartemisinin (by 18%; 90% CI 0.74–0.91) but increased lumefantrine (2.75‐fold; 90% CI 2.46–3.08) at steady state. Co‐administration of artemether/lumefantrine had no effect on etravirine, darunavir or ritonavir AUC. No drug‐related serious adverse events were reported during the study. Conclusions Co‐administration of etravirine with artemether/lumefantrine may lower the antimalarial activity of artemether and should therefore be used with caution. Darunavir/ritonavir can be co‐administered with artemether/lumefantrine without dose adjustment but should be used with caution.